- #1

- 1,011

- 0

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter Miike012
- Start date

- #1

- 1,011

- 0

- #2

pasmith

Homework Helper

- 1,992

- 627

My solution

d. [itex]\forall x[/itex] [itex]\exists y[/itex](F(x)^S(y) → [itex]\neg A(y,x)[/itex])

e. [itex]\exists x[/itex] [itex]\forall y[/itex](F(x)^S(y) → [itex]\neg A(y,x)[/itex])

f.[itex]\exists x[/itex] [itex]\forall y[/itex](S(x)^F(y) → A(x,y))

For d: You have "for every faculty member, there is a student who has not asked a question of that faculty member". That's not equivalent to "some student has not asked a question of any faculty member", because in the first it might not be the same student in each case. You need to swap the quantifiers.

The others appear to be correct.

Share: